A Study on Recent Trends for Guest Satisfaction in Selected Hotels of Delhi - Hussain, Sarah; Khanna, Kavita (Prabandhan: Indian Journal of Management, 2016)
Guest satisfaction is an ever evolving phenomenon for the hotel industry. With fast changing technology and globalization, the hotel industry caters to guests from all over the world, belonging to different segments and demography. The challenge is to keep the guests more than satisfied. This research was undertaken to study the current trends in guest satisfaction in five star deluxe hotel segment in Delhi. The study analyzed the gaps between hotel employees and guests' perception of importance and performance of different areas of hotels. Popular methods of guest feedback collection were also dealt with. The study shall contribute to the knowledge pool for academicians and provide an impetus to hotel management to evolve as per the guests' needs.